The first cultivated representatives of the actinobacterial lineage OPB41 isolated from subsurface environments constitute a novel order Anaerosomatales - Khomyakova, Maria A.; Zavarzina, Daria G.; Merkel, Alexander Y.; Klyukina, Alexandra A.; Pikhtereva, Valeria A.; Gavrilov, Sergey N.; Slobodkin, Alexander I. (Frontiers in Microbiology, 2022)
The continental subsurface harbors microbial populations highly enriched in uncultured taxa. OPB41 is an uncultured order-level phylogenetic lineage within the actinobacterial class Coriobacteriia. OPB41 bacteria have a wide geographical distribution, but the physiology and metabolic traits of this cosmopolitan group remain elusive. From two contrasting subsurface environments, a terrestrial mud volcano and a deep subsurface aquifer, located in the central part of Eurasia, within the Caucasus petroleum region, we have isolated two pure cultures of anaerobic actinobacteria belonging to OPB41. The cells of both strains are small non-motile rods forming numerous pili-like appendages. Strain M08DHBT is mesophilic, while strain Es71-Z0120T is a true thermophile having a broad temperature range for growth (25–77oC). Strain M08DHBT anaerobically reduces sulfur compounds and utilizes an aromatic compound 3,4-dihydroxybenzoic acid. Strain Es71-Z0120T is an obligate dissimilatory Fe(III) reducer that is unable to utilize aromatic compounds. Both isolates grow lithotrophically and consume molecular hydrogen or formate using either thiosulfate, elemental sulfur, or Fe(III) as an electron acceptor. Genomes of the strains encode the putative reductive glycine pathway for autotrophic CO2 fixation, Ni-Fe hydrogenases, putative thiosulfate/polysulfide reductases, and multiheme c-type cytochromes presumably involved in dissimilatory Fe(III) reduction. We propose to assign the isolated strains to the novel taxa of the species–order levels and describe strain M08DHBT as Anaerosoma tenue gen. nov., sp. nov., and strain Es71-Z0120T as Parvivirga hydrogeniphila gen. nov., sp. nov., being members of Anaerosomatales ord. nov. This work expands the knowledge of the diversity, metabolic functions, and ecological role of the phylum Actinomycetota.